Test construction and validation procedures of senior secondary schools’ mathematics teachers of Kano Central Senatorial District, Nigeria - Bashir Mohammed Ibrahim; Mohammad Ibrahim Sani (Eureka: Journal of Educational Research, 2024)
The purpose of this study was to assess competence in test construction and validation procedures of senior secondary schools’ mathematics teachers of Kano Central Senatorial District, Kano State, Nigeria. The study adopted survey design. The population of the study was 864 mathematics teachers. A sample of 110 mathematics teachers was drawn using Research advisor table for determining the sample size with 0.05 degree of accuracy at 95% confidence level. Simple random sampling technique was used for the study. The instrument for data collection was Mathematics Test Construction and Validation Questionnaire (MTCVQ). Cronbach alpha was used to determine the reliability coefficient of 0.76. The data collected were analysed using descriptive and inferential statistics. Mean and standard deviation were used to answer the research questions, while Independent sample t-test and Analysis of Variance were used to test the hypotheses. Findings revealed that, test construction procedure of mathematics teachers based on professional training (t=5.800, p-value=0.000), years of working experience (F=3.045, p-value=0.032) and validation procedure of mathematics teachers based on school type (t= -2.381, p-value=0.019) was significant. It further revealed that, validation procedures did not differ significantly based on educational qualifications (F=1.617, p-value=0.190). It was recommended among others that both trained and untrained mathematics teachers should put these basic and fundamental test construction and validation procedures mentioned in this study which formed the items in the questionnaire into practice.